Aphrodisiac property of aqueous and methanolic extracts of Raphia vinifera (Arecaceae) in sexually experienced male rats - Pierre Watcho; Fred Lih; Patrick Brice Defo Deeh; Modeste Wankeu-Nya; Esther Ngadjui; Georges Romeo Fozing Bonsou; Albert Kamanyi; Pierre Kamtchouing (Shahid Sadoughi University of Medical Sciences, 2019)
Background Raphia vinifera (Arecaceae) is a medicinal plant commonly used as a sexual enhancer. Objective To investigate the aphrodisiac potential of aqueous extract (AE) and methanolic extract (ME) of R. vinifera in sexually experienced male rats. Materials and Methods Thirty male Wistar rats were randomly distributed into six groups (5 rats per group) and administered for 14 days with distilled water (10 ml/kg), sildenafil citrate (1.44 mg/kg), and AE or ME of R. vinifera (100 or 500 mg/kg). The copulatory activity was tested on days 0, 7, and 14 using receptive females. Further, on day 14, rats were sacrificed and biochemical analyses (testosterone, total protein, and acid phosphatase) were performed. Results Sildenafil citrate significantly decreased the intromission latency (day 14, p = 0.04) and frequency (days 7 and 14, p = 0.03) but increased the mount frequency (day 14, p = 0.04), compared with control. Remarkably, R. vinifera enhanced the sexual activity by significantly decreasing the intromission latency (AE and ME, 500 mg/kg, day 14, p = 0.04) and increasing the mount frequency (AE and ME, 100 mg/kg, day 7, p = 0.02) compared with control. Moreover, R. vinifera improved plasmatic (AE, 100 mg/kg, p = 0.03; AE, 500 mg/kg, p = 0.001; ME, 100 mg/kg, p = 0.01) and testicular (AE, 100 mg/kg, p = 0.001; AE, 500 mg/kg, p = 0.01; ME, 100 mg/kg, p = 0.001; ME, 500 mg/kg, p = 0.01) testosterone levels as well as plasmatic total proteins concentration (ME, 500 mg/kg, p = 0.04). Conclusion These findings showed that R. vinifera possesses an aphrodisiac property which could further justify its folkloric use in traditional medicine as a sexual enhancer.